Endothelial function and insulin resistance in early postmenopausal women with cardiovascular risk factors: importance of ESR1 and NOS3 polymorphisms. - Ruth Clapauch (PLoS ONE, 2014)
Cardiovascular benefits from estradiol activation of nitric oxide endothelial production may depend on vascular wall and on estrogen receptor alpha (ESR1) and nitric oxide synthase (NOS3) polymorphisms. We have evaluated the microcirculation in vivo through nailfold videocapillaroscopy, before and after acute nasal estradiol administration at baseline and after increased sheer stress (postocclusive reactive hyperemia response) in 100 postmenopausal women, being 70 controls (healthy) and 30 simultaneously hypertensive and diabetic (HD), correlating their responses to PvuII and XbaI ESR1 polymorphisms and to VNTR, T-786C and G894T NOS3 variants. In HD women, C variant allele of ESR1 Pvull was associated to higher vasodilatation after estradiol (1.72 vs 1.64 mm/s, p = 0.01 compared to TT homozygotes) while G894T and T-786C NOS3 polymorphisms were connected to lower increment after shear stress (15% among wild type and 10% among variant alleles, p = 0.02 and 0.04). The G variant allele of ESR1 XbaI polymorphism was associated to higher HOMA-IR (3.54 vs. 1.64, p = 0.01) in HD and higher glucose levels in healthy women (91.8 vs. 87.1 mg/dl, p = 0.01), in which increased waist and HOMA-IR were also related to the G allele in NOS3 G894T (waist 93.5 vs 88.2 cm, p = 0.02; HOMA-IR 2.89 vs 1.48, p = 0.05). ESR1 Pvull, NOS3 G894T and T-786C polymorphism analysis may be considered in HD postmenopausal women for endothelial response prediction following estrogen therapy but were not discriminatory for endothelial response in healthy women. ESR1 XbaI and G894T NOS3 polymorphisms may be useful in accessing insulin resistance and type 2 diabetes risks in all women, even before menopause and occurrence of metabolic disease.